De novo genome assembly of the red silk cotton tree (Bombax ceiba). Issue 5 (10th May 2018) - Gao, Yong; Wang, Haibo; Liu, Chao; Chu, Honglong; Dai, Dongqin; Song, Shengnan; Yu, Long; Han, Lihong; Fu, Yi; Tian, Bin; Tang, Lizhou
Abstract: Background: Bombax ceiba L. (the red silk cotton tree) is a large deciduous tree that is distributed in tropical and sub-tropical Asia as well as northern Australia. It has great economic and ecological importance, with several applications in industry and traditional medicine in many Asian countries. To facilitate further utilization of this plant resource, we present here the draft genome sequence for B. ceiba . Findings: We assembled a relatively intact genome of B. ceiba by using PacBio single-molecule sequencing and BioNano optical mapping technologies. The final draft genome is approximately 895 Mb long, with contig and scaffold N50 sizes of 1.0 Mb and 2.06 Mb, respectively. Conclusions: The high-quality draft genome assembly of B. ceiba will be a valuable resource enabling further genetic improvement and more effective use of this tree species.